Combustion, performance, and emission behaviors of biodiesel fueled diesel engine with the impact of Alumina Nanoparticle as an additive - Kumar, S. Senthil; K., Rajan; Vinayagam, Mohanavel; Manickam, Ravichandran; Rajendran, Parvathy; Rashedi, Ahmad; Sharma, Abhishek; Khan, Sher Afghan; Afzal, Asif (MDPI, 2021)
The objective of this research work is to evaluate the performance, combustion, and exhaust emissions of a variable compression ratio diesel engine utilizing diesel 25% rubber seed biodiesel mixture (B25) blended with 25 ppm and 50 ppm of alumina nanoparticle running with different operating conditions. An ultrasonicator was used to make uniform dispersion of alumina (Al) nanoparticles in the diesel–biodiesel mixture. Biodiesel mixture blended with nanoparticles has physicochemical characteristics that are comparable to ASTM (American Society for Testing and Materials) D6751 limitations. The results revealed that the B25 exhibited a lower cylinder peak pressure and lower HRR (heat release rate) than diesel at maximum power. BTE (brake thermal efficiency) of B25 is 2.2% lower than diesel, whereas BSFC of B25 is increased by 6% in contrast to diesel. Emissions of HC (hydrocarbon), CO (carbon monoxide), and smoke for B25 were diminished, while emissions of NOx (nitrogen oxide) were higher at maximum power. Further, the combustion and performance of diesel engines were improved with the inclusion of alumina nanoparticles to biodiesel blends. In comparison to B25, BTE of B25 with 50% alumina nanoparticles (B25Al50) mixture was enhanced by 4.8%, and the BSFC was diminished by 8.5%, while HC, CO, and smoke were also diminished by 36%, 20%, and 44%, respectively. At peak load, the maximum cylinder pressure and HRR of B25 were improved by 4.2% and 6.7%, respectively, with the presence of 50% alumina nanoparticles in a biodiesel blend (B25Al50).